Perception of intertexts and identification of the cultural circle in publicistic texts by Rimvydas Valatka - Valotka, Audrius (Lietuvių kalba, 2016)
The article analyses the strategies of employing intertexts –primarily, allusions – in contemporary Lithuanian media. The study relies on the idea that recognition of an allusion in text and its appropriate interpretation shows that both the author and the reader belong to the same cultural circle which can be identified on the basis of age, education, field of interests and other factors. In order to reach her/his audience, a publicist has to write in the language that the audience understands best. Therefore, if a reader fails to recognise allusions or s/he interprets them differently than intended, s/he is not part of the cultural circle. The selected method of the study was testing respondents in order to determine how effectively allusions are recognised and interpreted by a small yet significant segment of the readership, namely, students aged 18 to 20. The respondents had to identify and interpret allusions in fifty sentences collected from articles by Rimvydas Valatka, a distinguished Lithuanian publicist, whose writings are characteristic of rich rhetorical expression. The results demonstrate that only about one fourth of respondents interpret publicistic allusions adequately:Adequate interpretation – 27%, unreasonable interpretation – 25%, no interpretation – 48%.The statistics of the recognition and interpretation of allusions used in the texts fluctuates considerably in different areas of precedent texts: Biblical allusions – 37%, folklore allusions – 32%, historical allusions – 12%, cinematographic allusions – 49%, cultural allusions – 25%, literary allusions – 25%.It is possible to conclude that numerous intertexts used by Rimvydas Valatka are not targeted at the student-age audience, except for the obvious shift from the Soviet- and Russian-specific items (only 11% of precedent texts that belong to this category were identified by respondents) and that this segment of the readership remains in the periphery of Rimvydas Valatka’s cultural circle.
Keywords: intertextuality; precedent texts; cultural circle; allusion; publicistic text